Analisis Pengendalian Risiko Kecelakaan Kerja Menggunakan Metode Job Safety Analysis (JSA) : (Studi Kasus: PT Madubaru PG-PS Madukismo) - Bima Putra Pranoto; ferida yuamita (Politeknik Kampar, 2025)
The optimal implementation of Occupational Safety and Health (OSH) is a crucial aspect in ensuring worker safety and maintaining smooth production processes in the sugar processing industry. At PG Madukismo, there were 23 recorded work accidents during the 2022 milling season, which increased to 45 cases in 2023, with 7 incidents occurring in the milling station. The rise in accident rates is attributed to workers' non-compliance with safety procedures, such as the use of Personal Protective Equipment (PPE), and substandard working environment conditions. This study aims to identify potential hazards and analyze work risks at the milling station of PG Madukismo using the Job Safety Analysis (JSA) method. The method involves breaking down each work activity, identifying hazards, assessing risk levels based on likelihood and severity, and determining appropriate control measures. The results show that several work activities pose high-risk levels, primarily due to excessive noise, mechanical hazards from milling machines, and inadequate lighting. These findings underscore the need to enhance supervision, provide OSH training, and improve workplace conditions to establish a safer, healthier, and more productive work environment.